Promoting awareness of neonatal menstruation. (4th March 2017) - Bianchi, Paola; Benagiano, Giuseppe; Brosens, Ivo
Abstract: Neonatal uterine bleeding (NUB) has been carefully studied in the past through case reports, small series, clinical cohort studies, pathology investigations of fetal and neonatal. Following a historical recount, this review summarizes biological mechanisms conditioning NUB, starting from the persistence till birth of an 'ontogenetic progesterone resistance' (OPR), causing decreased responsiveness of target tissues to bioavailable progesterone. Several pregnancy-related conditions, such as preeclampsia, fetal growth restriction, prematurity, post-maturity and even Rhesus or ABO incompatibility, influence the occurrence of NUB. It seems therefore that the phenomenon is precipitated by chronic fetal distress. When present, OPR may persists until telarche; as a consequence, if pregnancy occurs in early teenage, the disorder known as "defective deep placentation" may ensue, increasing the risk of obstetrical syndromes. In the presence of NUB, retrograde shedding into the peritoneal cavity of endometrial stem/progenitor and niche cells may occur. There, given the right environment, these cells can survive and become activated at the time of telarche, causing the specific phenotype of early-onset endometriosis. In conclusion, neonatal menstruation is a fetal distress indicator and can alter the incidence of a variety of pathological conditions later in life. For this reason, it should be carefully recorded and the parents informed.